1999
DOI: 10.1002/(sici)1098-2795(199905)53:1<27::aid-mrd4>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Defining regions of the Y‐chromosome responsible for male infertility and identification of a fourth AZF region (AZFd) by Y‐chromosome microdeletion detection

Abstract: Cytogenetic and molecular deletion analyses of azoospermic and oligozoospermic males have suggested the existence of AZoospermia Factor(s) (AZF) residing in deletion intervals 5 and 6 of the human Y-chromosome and coinciding with three functional regions associated with spermatogenic failure. Nonpolymorphic microdeletions in AZF are associated with a broad spectrum of testicular phenotypes. Unfortunately, Sequence Tagged Sites (STSs) employed in screening protocols range broadly in number and mapsite and may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 0 publications
1
78
0
4
Order By: Relevance
“…The prevalence of polymorphisms may vary between the different populations. This assumption has been supported by a very recent study, which found a single STS missing for sY84 in Asian fertile men (1/117) (12), even though this STS previously was suggested not to be polymorphic (5). Thus, the pathogenetic significance of these single missing STSs remains to be determined.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The prevalence of polymorphisms may vary between the different populations. This assumption has been supported by a very recent study, which found a single STS missing for sY84 in Asian fertile men (1/117) (12), even though this STS previously was suggested not to be polymorphic (5). Thus, the pathogenetic significance of these single missing STSs remains to be determined.…”
Section: Discussionmentioning
confidence: 83%
“…A high frequency of Y microdeletions has been reported (up to 55%) in men having oligozoospermia or azoospermia (5). An association between testicular cancer and male infertility has been studied and reported in many studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compositions of the STSs and the size of their base pairs for each of the multiplex primers are shown in Table 1. These STSs were derived from the map by Vollrath et al [22], Henegariu et al [4], Reijo et al [16], and Kent-First et al [6]. The primer pairs in a multiplex di ered at least 22 base pairs in length from each other to make the screening easier and more e cient.…”
Section: Materials/methodsmentioning
confidence: 99%
“…In 1999, Kent-First et al divided AZF into three regions: AZFa, AZFb and AZFc. Among them, AZFb and AZFc possess an overlapping area of about 1.5 Mb, only the AZFa region is relatively independent [24][25][26]. Microdeletion in the AZF region is closely related to the male infertility, as it is one of the most common molecular genetic causes of azoospermia or severe oligozoospermia.…”
Section: Discussionmentioning
confidence: 99%